2016
DOI: 10.1016/j.appet.2015.11.013
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitory control training for appetitive behaviour change: A meta-analytic investigation of mechanisms of action and moderators of effectiveness

Abstract: Rationale Both cue avoidance training (CAT) and inhibitory control training (ICT) reduce alcohol consumption in the laboratory. However, these interventions have never been directly compared and their mechanisms of action are poorly understood. Objectives We compared the effects of both types of training on alcohol consumption and investigated if they led to theoretically predicted changes in alcohol avoidance (CAT) or alcohol inhibition (ICT) associations and changes in evaluation of alcohol cues. Methods Hea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

18
298
3
4

Year Published

2016
2016
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 309 publications
(323 citation statements)
references
References 63 publications
18
298
3
4
Order By: Relevance
“…In addition, the facets of executive function that most strongly predict childhood metabolic outcomes remains an active area of research. Inhibitory control has been perhaps the most active area of investigation to date [20, 22, 23, 26, 83], but others domains, such as emotion regulation [24], may also play a role and require further study. Understanding the extent to which children’s executive function and general self-regulation relate to appetite and self-regulation in the context of eating will be important and is an active area of research [84–86].…”
Section: Evidence Linking Self-regulation In Young Children To Risk Fmentioning
confidence: 99%
“…In addition, the facets of executive function that most strongly predict childhood metabolic outcomes remains an active area of research. Inhibitory control has been perhaps the most active area of investigation to date [20, 22, 23, 26, 83], but others domains, such as emotion regulation [24], may also play a role and require further study. Understanding the extent to which children’s executive function and general self-regulation relate to appetite and self-regulation in the context of eating will be important and is an active area of research [84–86].…”
Section: Evidence Linking Self-regulation In Young Children To Risk Fmentioning
confidence: 99%
“…For example, recent studies have shown that training individuals to inhibit simple motor responses to images of food, using either the stop-signal or go/no-go tasks, can result in the decreased consumption of that food (Houben and Jansen, 2011, Houben and Jansen, 2015, Houben, 2011, Lawrence et al., 2015a, Veling et al., 2011), healthier food choices (Koningsbruggen et al., 2014, Veling et al., 2013a, Veling et al., 2013b) and even weight loss (Lawrence et al., 2015b, Veling et al., 2014). Three recent meta-analyses have demonstrated small to medium effect sizes for the effect of food-related inhibition training compared to control training (Allom et al., 2015, Jones et al., 2016; Turton, Bruidegom, Cardi, Hirsch, & Treasure, 2016). However, there are some inconsistencies in training effects and several questions remain unanswered.…”
Section: Introductionmentioning
confidence: 99%
“…In the two studies presented here, we sought to investigate the mechanisms involved in these training effects and whether such effects are reliant upon stimulus-specific associations between the stop-signal and the trained food. For example, inhibition training may be most effective when strong automatic associations are formed between the foods and a successful stop response (Jones et al., 2016). Stimulus-specific training effects would therefore result in reduced consumption of the trained foods only, whereas generalised effects could see reduced consumption of other unhealthy foods or even healthy foods.…”
Section: Introductionmentioning
confidence: 99%
“…For example, consistent pairing of food-related pictures to stopping in a go/no-go or stop-signal paradigm reduces subsequent food consumption (e.g., Houben & Jansen, 2011;Lawrence, Verbruggen, Morrison, Adams, & Chambers, 2015), and may even lead to weight loss Veling, van Koningsbruggen, Aarts, & Stroebe, 2014). Recent meta-analyses indicate that no-go/stop training has small but robust effects on food and alcohol consumption (Allom, Mullan, & Hagger, 2015;Jones et al, 2016). Go/no-go training may have larger effects on subsequent appetitive behaviour than stop-signal training.…”
Section: Applications Of Automatic Inhibitionmentioning
confidence: 99%